Le rire des féministes - Laufer, Laurie (2020)
In France, in the wake of the movement of May 68, the Women's Liberation Movement (MLF) spontaneously and joyfully emerged, initiated by Antoinette Fouque and Monique Wittig. In their debates and their critical rereadings of the Freudian and Lacanian texts, they think afresh the discourse and theory of psychoanalysis on "Women", "the feminine", "female sexuality", and "sex difference". The theoretical dogmas concerning "the black continent" romantically evoked by Freud are revisited, and even reversed. The quarrels over the very term of "feminism" produce and give way to other discourses.Freud always considered that psychoanalytical theory was open to revision and Lacan that psychoanalysis would benefit from being in 'extension'. What happens when psychoanalytic theory and practice meet feminist discourses? Does this encounter imply that the horizon should open up for psychoanalytical discourse, its theory and practice? Can an opening, a revision then take place? A dogma, a new joy in analytical practice?